A MURDER MYSTERY SOLVED BY MITOCHONDRIAL DNA SEQUENCING (Journal of Forensic Medicine & Toxicology, 2025)
The present case study emphasises the important role of mitochondrial DNA (mtDNA) analysis in forensic investigations, particularly in situations where conventional nuclear DNA (nDNA) analysis is challenging due to sample degradation. In this case, heavily degraded skeletal remains yielded no usable nDNA profile, yet mtDNA analysis provided conclusive evidence, establishing a maternal link between the remains and the alleged mother. The study highlights the control region sequencing of mtDNA, which revealed an identical haplotype between the deceased’s bone sample and the alleged mother’s blood sample. The findings emphasize mtDNA’s complementary role in forensic casework, particularly in scenarios involving degraded, low-quantity samples, or cases requiring maternal lineage verification. The study advocates for the routine inclusion of mtDNA analysis in forensic protocols, contributing to the growing recognition of its significance in modern forensic science.
Keywords: Mitochondrial DNA (mtDNA); Forensic identification; Degraded samples; Skeletal remains; Maternal lineage